2008
DOI: 10.2463/mrms.7.85
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Endolymphatic Hydrops at 3 Tesla Using 3D-FLAIR with Intratympanic Gd-DTPA Administration

Abstract: Purpose: Visualization of endolymphatic hydrops by 3-dimensional ‰uid-attenuated inversion recovery-FLAIR using conventional turbo-spin-echo (3D-FLAIR-CONV) after intratympanic injection of Gd-DTPA has been reported in patients with M áeni àere's disease. Compared to 3D-FLAIR-CONV used in previous studies, the addition of a variable ‰ip-angle technique (3D-FLAIR-VFL) enables very long echo trains and, therefore, shorter scan times. We evaluated whether 3D-FLAIR-VFL could replace 3D-FLAIR-CONV in detecting endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…In addition, the IT-method is a useful preliminary prediction tool of drug distribution to the inner ear, such as the distribution of gentamicin and steroids after intratympanic administration. [11][12][13][14] For the patients with an inner ear disorder who have restrictions in daily life caused by vertigo or hearing loss, further imaging investigation of the inner ear and preliminary prediction of drug distribution to the inner ear are extremely important matters to improve their quality of life. Therefore, the features of the IT-method observed in the present study warrant considering their advantage for the close investigation of inner ear disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the IT-method is a useful preliminary prediction tool of drug distribution to the inner ear, such as the distribution of gentamicin and steroids after intratympanic administration. [11][12][13][14] For the patients with an inner ear disorder who have restrictions in daily life caused by vertigo or hearing loss, further imaging investigation of the inner ear and preliminary prediction of drug distribution to the inner ear are extremely important matters to improve their quality of life. Therefore, the features of the IT-method observed in the present study warrant considering their advantage for the close investigation of inner ear disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments by using intratympanic gadolinium injection, gadolinium was diluted 8-fold with saline, which is the concentration of gadolinium used in the previous and the present human studies, and showed no marked effect on the stria vascularis. 28 The reports describing intratympanic gadolinium injection in human subjects have been published from several institutions, including ours, [11][12][13][14][15][23][24][25][29][30][31] and no marked side effects in the inner ear relating to intratympanic gadolinium injection have been reported on clinical application at present, to the best of our knowledge. In addition, intravenously administered gadolinium has been reported to infiltrate inner ear perilymph, 16,17,22,23 and no marked side effects in the inner ear relating to IV gadolinium injection have been reported in the clinical application at present.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The features of this variable ‰ip-angle sequence have been reported elsewhere. 18,22 This sequence allows the use of very long echo-train lengths, in the range of 100-200, without severe blurring, while maintaining contrast similar to that of 3D-FLAIR-CONV, even with a long eŠective echo time.…”
Section: Mr Imagingmentioning
confidence: 99%
“…We acquired 3D images in all patients: 3D-constructive interference in the steady state (CISS); 3D-FLAIR by conventional turbo spin echo (3D-FLAIR-CONV); 1,16 3D-FLAIR by variable ‰ip angle turbo spin echo (3D-FLAIR-VFL); 18 and 3D-inversion recovery with real reconstruction (3D-real IR) 19 as well as TI scout images. To evaluate signal intensity, we analyzed 3D-FLAIR-VFL and TIscout images because the 0.8-mm slice thickness of the 3D-FLAIR-VFL protocol is less susceptible to partial volume averaging artifact than the 2-mm slice thickness of 3D-FLAIR-CONV.…”
Section: Mr Imagingmentioning
confidence: 99%